A multicenter, prospective, observational study examining the impact of risk factors, such as BMI and waist circumference, on quality of life improvement and clinical response in moderate‐to‐severe plaque‐type psoriasis patients treated with infliximab in routine care settings of Greece. (20th April 2018) - Petridis, A.; Panagakis, P.; Moustou, E.; Vergou, T.; Kallidis, P.; Mandekou‐Lefaki, I.; Chaidemenos, G.; Sotiriadis, D.; Alexopoulou, G.; Haratsis, Y.; Antoniou, C.
Abstract: Background: Obesity has been associated with moderate‐to‐severe plaque psoriasis severity and PASI 75 response attainment of biologic therapies, but findings are inconsistent. Objective: This study aimed to examine the association of body mass index (BMI) and waist circumference (WC) on disease severity, to identify potential patient characteristics associated with response attainment and to assess the impact of infliximab on the patients' health‐related quality of life (HRQoL) among infliximab‐treated patients in the routine care setting of Greece. Methods: This was a multicenter, prospective, observational study of adult moderate‐to‐severe plaque psoriasis patients who had initiated treatment with originator infliximab within 2 weeks prior to enrolment. Postenrolment visits occurred at 14 ± 4, 30 ± 4 and 54 ± 4 weeks following treatment onset. Results: Between October 2012 and June 2014, 136 eligible patients (62.5% males) with a median age of 48.6 years, BMI of 29.6 kg/m 2 and WC of 107.0 cm at enrolment were recruited by 21 dermatology hospital/private offices. All patients had received prior psoriasis treatment(s); 62.5% were biologic‐naïve. Mean baseline psoriasis area severity index (PASI) and Dermatology Quality of Life Index (DLQI) scores were 23.4 ± 13.6 and 15.0 ± 8.3, respectively. A low correlation was observed between WC at enrolment and baseline PASI [ρ = 0.324 ( P < 0.001)]. Over a median 48.4 weeks of infliximab exposure, 89.3% of the per protocol set achieved a PASI 75 response. At 14, 30 and 54 weeks, the PASI 75 attainment rate was 66.4%, 74.8% and 76.6%, respectively; the clinically meaningful DLQI improvement (≥5 point decrease) rate was 68.9%, 75.7% and 69.8%, respectively. BMI category and abdominal obesity at enrolment did not impact PASI 75 or DLQI improvement rate attainment. Conclusion: In the routine care of Greece, infliximab reduced disease activity and improved the quality of life of moderate‐to‐severe psoriasis patients through 1 year of treatment, independent of their BMI and WC.